The Extent of Compliance with the Requirements of IFRS 7: A Comparative Study between Palestinian and Jordanian Banks - Heba N. ASSAD (Communications of International Proceedings, 2022)
IFRS 7 focuses on financial instrument disclosures. It is generally assumed that organizations need to provide disclosure in annual financial reporting which enables stakeholders to determine the significance of financial instruments to a corporation's financial condition and performance. This study aims to evaluate the degree to which Palestinian and Jordanian listed banks on the Palestine Stock Exchange (PEX) & the Amman Stock Exchange, respectively, complied with the requirements of IFRS 7 from 2014 to 2019. To evaluate the degree of conformity with IFRS 7 criteria in banks' annual financial reporting, a scorecard with 77 components was developed. Using the SPSS software, the results showed that a sample of Jordanian banks comply with the IFRS 7 requirements by a mean of 66.44%, while Palestinian banks comply with these requirements by an amount of 60.95%. Furthermore, the results show a significant difference in the extent of compliance with IFRS 7 among Jordanian and Palestinian banks.
Keywords: IFRS7; Financial Instruments; Jordan; Palestine; Disclosures